(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Learning education aid is a government program aimed at assisting improverished children with high achievement in completing their 12-year compulsory education by assisting them in gaining access to adequate educational resources. Every school undertakes screening processes to determine potential scholarship applicants. This selection is done to ensure that the students who receive this help are those who are eligible. Concerning the difficulties faced by the selection committee, such as the difficulty in swiftly determining who is chosen as a candidate for aid receivers based on subjective or uncertain factors. To overcome these problems, a decision support system was designed using the Simple Additive Weighting (SAW) method, which is a simple ranking method by finding a weighted sum based on predetermined assessment criteria. Total Income of Parents, Number of Dependents of Parents, Value of Report Cards, Personality, Achievements, Poor People, Number of Alpha Student Attendances, and Received Government Program assistance were the criteria used. The goal of this research is to develop a decision-making tool that will aid the school in selecting children who will receive assistance. The method used can get the first rank with 18.51 being the top average value.